2021
DOI: 10.3390/cancers13174455
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 as a Prognostic Biomarker in Invasive Breast Cancer

Abstract: The advent of molecular medicine has transformed breast cancer management. Breast cancer is now recognised as a heterogenous disease with varied morphology, molecular features, tumour behaviour, and response to therapeutic strategies. These parameters are underpinned by a combination of genomic and immunohistochemical tumour factors, with estrogen receptor (ER) status, progesterone receptor (PgR) status, human epidermal growth factor receptor-2 (HER2) status, Ki-67 proliferation indices, and multigene panels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 153 publications
2
61
0
1
Order By: Relevance
“…These results revealed that IFM-GA+laser group exhibited good anti-tumor efficacy. Then, we conducted the ki67 assessment, a test principally used for estimation of cancer prognosis [39] . The results in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results revealed that IFM-GA+laser group exhibited good anti-tumor efficacy. Then, we conducted the ki67 assessment, a test principally used for estimation of cancer prognosis [39] . The results in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the smaller sample size compared to the wider sample size in other studies is a great contributing aspect to the complementary results in our study. Moreover, even though the predictability and prognostication of Ki67 as a biomarker is widely acknowledged, we were unable to investigate them in our study as disease free survival rates were unobtainable due to most patients being lost to follow up [ 20 ]. Finally, the relatively incomplete medical history concerning some patients was another limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological differences between GSM and classical GBM cannot be overlooked. GSM is rich in sarcoma components, which were insensitive to RT and chemotherapy [30], which is related to minimal statistical effectiveness.…”
Section: Discussionmentioning
confidence: 99%